Victim’s Involvement Model in Children Legal Process Based on Law no. 11/2012 on Children Criminal Justice System - Oheo K Haris; Ali Risky (Yuridika, 2019)
The enactment of Law N0. 11/2012 on Children Criminal Justice System is a new hope for the rights of the victims of a crime. This Law has given a huge opportunity to the victims by means of the concept of restorative justice. This paper seeks to offer a model of victim’s involvement which is implementable either outside or inside of the judicial system. Firstly, accessibility for the victim in this law has placed the concept of restorative justice. The model of restorative justice offered in this law is the gate for the crime victim who fought for their rights. Restorative justice was essentially stands between the victim and the offender and focuses on the effects of crimes. Secondly, the term diversion is the transfer of resolution for the process of the juvenile case from the judicial system to outside of the criminal system. Togetherness for all of the involved groups is a better solution in certain case as it can solve problem and create better unprecedented bindings. This attempt is in order to seek solution, reconciliation, and not to seek revenge for a criminal offence. Thirdly, victim’s invovelment in criminal system allows for witnesses to come forward. But they should have legal protection and should avoid bad label. The next model is an opportunity for the juvenile victism before the court handing down the verdict.